Effects of Providing a Liquid Sensory Attractant to Suckling Pigs in Lactation and After Weaning on Post-Weaning Pig Performance - Madie R. Wensley; Ty Kim; Mike D. Tokach; Robert D. Goodband; Jason C. Woodworth; Joel M DeRouchey; Denny McKilligan; Nathan Upah; Jordan T. Gebhardt (Kansas Agricultural Experiment Station Research Reports, 2021)
A total of 28 litters (241 × 600, DNA) corresponding with 355 nursery pigs (241 × 600, DNA; initially 13.0 lb) were used in 42-d trial (17-d pre-weaning and 24-d post-weaning). This trial was conducted to determine the effect of providing a sensory attractant liquid (BlueLite Pro2Lyte; TechMix Global; Stewart, MN) to suckling pigs on the underline of sows after farrowing and in late lactation, and after weaning on post-weaning feed intake and growth. Treatments were arranged in a 2 × 2 × 2 factorial with main effects of: 1) pre-weaning treatment (without or with attractant); 2) postweaning treatment (without or with attractant); and 3) body weight category (light or heavy). Overall, pre-weaning liquid sensory attractant did not have a significant effect on piglet weaning weight or post-weaning growth performance. Likewise, post-weaning application had limited effects on the growth performance of pigs after weaning. Liquid sensory attractant pre-weaning increased the percentage of lightweight pigs that lost weight from weaning to d 3 by approximately 16 percentage points, whereas liquid sensory attractant pre-weaning decreased the percentage of heavyweight pigs that lost weight after weaning by approximately 17 percentage points (pre-weaning treatment and BW category interaction,P= 0.003). This interaction diminished by d 7. Significance was also detected for the main effect of BW category. A greater percentage of heavyweight pigs lost weight on d 3 (P= 0.007) and d 7 (P= 0.051) compared to lightweight pigs. In summary, liquid sensory attractant that was applied pre- and post-weaning had limited effects on the growth performance of pigs; however, varying responses were observed for the percentage of pigs that lost weight immediately after weaning. Strategies to reduce the number of pigs that lose weight after weaning warrant further investigation.
Keywords: performance; pig; sensory attractant; suckling; weaning